2016
DOI: 10.1080/10428194.2016.1213829
|View full text |Cite
|
Sign up to set email alerts
|

BiallelicATMalterations detected at diagnosis identify a subset of treatment-naïve chronic lymphocytic leukemia patients with reduced overall survival similar to patients with p53 deletion

Abstract: The prognostic impact of biallelic ATM abnormalities (ATM mutation and concurrent 11q deletion) remains unknown. We studied ATM, BIRC3, SF3B1, and NOTCH1 genes in 118 treatment-naïve CLL patients at diagnosis. Patients with biallelic ATM alteration had a similar time to first treatment (TTFT) and shorter overall survival (OS) compared with patients with isolated 11q deletion and shorter TTFT and OS when compared to patients with wild-type ATM. Furthermore, biallelic ATM alteration (HR: 6.4; p ≤ 0.007) was sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…15 Deleterious mutations in the remaining allele of ATM or gain-of-function SF3B1 mutations in del(11q) patients have been shown to drive CLL oncogenesis, being associated with a worse prognosis. [15][16][17][18][19] Nevertheless, these mutations only account for 30% or 20% of del(11q) cases, respectively, leaving more than half of del(11q) patients with unknown second driver of the disease. Another high-risk-associated cytogenetic feature in CLL is the deletion of chromosome 17p13.1 (del(17p)), which appears in 4-10% of CLL cases at diagnosis 20,21 and in up to 40% of relapsing cases to chemoimmunotherapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Deleterious mutations in the remaining allele of ATM or gain-of-function SF3B1 mutations in del(11q) patients have been shown to drive CLL oncogenesis, being associated with a worse prognosis. [15][16][17][18][19] Nevertheless, these mutations only account for 30% or 20% of del(11q) cases, respectively, leaving more than half of del(11q) patients with unknown second driver of the disease. Another high-risk-associated cytogenetic feature in CLL is the deletion of chromosome 17p13.1 (del(17p)), which appears in 4-10% of CLL cases at diagnosis 20,21 and in up to 40% of relapsing cases to chemoimmunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been reported that monoallelic ATM deletion is not enough to cause a CLL‐like disease in mice 15 . Deleterious mutations in the remaining allele of ATM or gain‐of‐function SF3B1 mutations in del(11q) patients have been shown to drive CLL oncogenesis, being associated with a worse prognosis 15–19 . Nevertheless, these mutations only account for 30% or 20% of del(11q) cases, respectively, leaving more than half of del(11q) patients with unknown second driver of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in TP53, NOTCH1, SF3B1, and ATM and/or loss of ATM (11q22.3) in CLL/SLL have been reported to be associated with a worse prognosis. [27][28][29][30] The K1992T mutation in ATM in our patient has not been reported previously. As the K1992T ATM mutation seen in our patient occurs in the FAT domain, a critical regulator of ATM protein kinase activity, 31 it is possible that this alteration could alter ATM activity.…”
Section: Discussionmentioning
confidence: 49%
“…Moreover, it is desirable to examine both alleles of the TP53 and ATM genes, representing adverse prognostic factors. 30,[47][48][49] Integrative targeted NGS testing in CLL can overcome the drawbacks of parallel genetic tests by simultaneous analysis of multiple genetic markers, resulting in faster and consolidated interpretation of results. 24,25 In summary, our data extend the previous reports on CLL evolution and dynamics of genomic defects during the pretreatment period of the disease.…”
Section: Discussionmentioning
confidence: 99%